Optimalisasi Profit Penjualan Dengan Linear Programming Melalui Metode Simpleks Menggunakan Qm For Windows (Studi Kasus UD. Hasil Laut Prima Desa Prenduan) - Alifatul Fuaddiyah; Fiqih Rahman Hartiansyah; Moh. Wasil (Department of Mathematics, Faculty of Mathematics and Scince, Universitas Annuqayah, 2025)
This study aims to determine the right combination of resources in order to obtain the maximum amount of production to obtain optimal profits in the UD industry. Prima Sea Results Prenduan village. The analysis used is Linear programming through simplex method using Qm for Windows application. In this study there are 3 decision variables and 8 constraint functions. The decision variables used are jumbo, medium and stick rengginang. The constraints in this study are the raw materials used in the processing of rengginang. The results of this study indicate that the production and profits obtained are still not optimal, to achieve optimal profits, it must produce 12 pcs of rengginang stick with optimal profits reaching Rp. 2,435,616.00.